TECHNOLOGY PEDAGOGY CONTENT KNOWLEDGE (TPACK) (ANALISIS KONSEP & MODEL PEMBELAJARAN) - Helda Kusuma Wardani (Universitas Islam Malang, 2022)
A literature analysis was conducted on TPACK to corroborate the concept, which is new to learning practices in elementary schools. This learning principle is being vigorously disseminated through various scientific forums, and is most visibly highlighted in Teacher Professional Education (PPG) for elementary classroom teachers. TPACK is knowledge that includes technology knowledge (TK), pedagogy knowledge (PK), and content knowledge (CK) as its three main elements. These three elements intersect with each other which gives rise to 4 (four) other main elements of TPACK. Thus, in learning practices, a professional teacher is required to be able to apply the 7 (seven) main elements of TPACK. The implementation of TPACK learning principles must exist in the design, implementation, and assessment of learning carried out by teachers.